The effect of manganese on the microstructure and mechanical properties of leaded-tin bronze - Turhan, H; Aksoy, A; Kuzucu, V; Yildirim, MM (Elsevier Science Sa, 2001)
In this work, the effect of manganese (Mn) on microstructure and mechanical properties of leaded-tin bronze was studied by using scanning electron microscopy and energy dispersive spectroscopy techniques, and tensile, fatigue and adhesive wear tests. It was observed that Mn decreased the wear resistance at the beginning stage of wear and markedly increased the fatigue life by preventing the formation of brittle and fragile (Zn, Cu)S phase, but it did not affect importantly the yield point, tensile strength, elongation and hardness. It was concluded that leaded-tin bronzes containing Mn can be preferred in manufacturing of machine elements in which fatigue is important. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: leaded-tin bronze; microstructure; wear; fatigue